Pengaruh Rebusan Daun Kelor Terhadap Penurunan Kadar Glukosa Darah Pada Penderita Diabetes Mellitus Di Wilayah Kerja Puskesmas Kartasura - Farda Masyta Putri; Yuli Widyastuti; Cemy Nur Fitria (STIKes Ibnu Sina Ajibarang, 2023)
Non-communicable diseases are one of the main causes of death in Indonesia, for example diabetes mellitus. Diabetes mellitus is a condition where blood sugar levels are above normal because the body does not produce enough insulin. One of the non-pharmacological treatments for diabetes mellitus is by giving Moringa leaf boiled water. To find out the results of whether there is an effect of giving Moringa leaf decoction on reducing blood glucose levels in patients with diabetes mellitus in the working area of the Kartasura Health Center. Two group pre-test and post-test research design. This research was conducted in Wirogunan Village in March-May 2023 as many as 22 respondents were divided into intervention groups and control groups. This study used non-probability sampling techniques with purposive sampling techniques. The instruments used in this study used observation sheets. The data obtained were then tested for normality using the Shapiro-Wilk Test. The data is then processed using the Mann-Whitney Test. The results of the Mann-Whitney Test showed that there was an average difference between the intervention group given Moringa leaf decoction and the control group who were not given Moringa leaf decoction with the results of a signification value of α<(0.05) (p = 0.001). There is an effect of Moringa leaf decoction on reducing blood glucose levels in patients with diabetes mellitus in Wirogunan Village with a p value: 0.001.